Management by walking about in achieving organizational excellence: The role of total quality management - Nson, Yilkes Danladi (Goodwood Publishing, 2024)
Purpose: This study evaluated the influence of Total Quality Management (TQM) on the relationship between Management by Walking Around (MBWA) and its dimensions on organizational excellence (OE). Research Methodology: This study adopted a detailed review of conceptual and empirical articles from high-impact journals related to the topic and authors’ experience. Results: A review of relevant studies reveals that management practices by walking around (MBWA) and its dimensions positively lead to organizational excellence. TQM mediates the relationship between MBWA and OE. Limitations: This study is limited to TQM, MBWA, and their dimensions in achieving organizational excellence. Contribution: This study provides a framework that can be used by corporate organizations, entrepreneurs, researchers, policymakers, community leaders, and governments to develop predictive models and empirical research to evaluate the influences of MBWA mediated by TQM in achieving organizational excellence. Therefore, providing quality products and services will improve the lives of people. Originality: This study addresses calls for further study of MBWA and TQM in achieving organizational excellence. This research provides further understanding of the TQM nexus by exploring its influence on the relationship between the dimensions of MBWA and organizational excellence within the context of developing countries. This study is the first to use TQM as a mediator between MBWA and OE. The originality of this study comes from the researcher's ability to pinpoint how an organization can adopt the practices of MBWA complemented by the long-standing innovative tradition of Japanese management to achieve quality and excellence.